COLEOBROCAS (INSECTA: COLEOPTERA) ASSOCIADAS À MADEIRA DE Tectona grandis LINN.F (LAMIACEAE) - Moura, Rogério Goularte; Berti Filho, Evoneo; Peres Filho, Otávio; Dorval, Alberto (REVISTA DE AGRICULTURA, 2015)
COLEOBROCAS (INSECTA: COLEOPTERA) ASSOCIADAS À MADEIRA DE Tectona grandis LINN.F (LAMIACEAE)